Data of Project on Atmospheric Circulation and Material Cycle in the Antarctic, Part 3. Backscattering Properties of Tropospheric Clouds and Aerosols Observed by a Lidar at Dome Fuji Station in 1997 - Hayashi, Masahiko; Sudo, Masaki; Shiraishi, Kouichi; Hirasawa, Naohiko; Yamanouchi, Takashi; Shibata, Takashi; Iwasaka, Yasunobu; Nagatani, Masahiro; Nakada, Akira (National Institute of Polar Research, 2004)
P(論文) departmental bulletin paper